Analysis of the Flow of the Connection Service Process to Achieve an Increase in Electricity Sales Using Application Design - Bayuaji, Rizal Bima; Suryani, Erma (Journal Research of Social Science, Economics, and Management, 2026)
The electricity customer connection process at PT PLN (Persero) continues to face significant operational challenges, including unintegrated data systems, limited real-time monitoring capabilities, and slow coordination between units. These challenges negatively impact overall service efficiency and electricity sales growth. This study aims to analyze the current customer connection workflow and design an integrated information system application to improve operational effectiveness and service quality. Using a descriptive qualitative approach, data was collected through direct observation, comprehensive operational document analysis, persona canvas, and Root Cause Problem Solving (RCPS) to identify business process issues. Diagnostic analysis revealed that severe data fragmentation and the absence of a centralized monitoring platform were the primary root causes of delays. To address these challenges, the Integrated Customer Connection (ICE) application was designed. This system seamlessly integrates the end-to-end workflow, including initial customer inquiries, technical surveys, field connection execution, and real-time operational monitoring through an interactive dashboard. The application design implementation successfully accelerated kWh sales, with a projected volume increase of 1,867,177 kWh by 2025. This achievement represents a 6.24% increase in sales compared to 2024, reaching a total volume of 13,178,583 kWh while drastically reducing the average service duration to 1.38 days. Furthermore, the software offers advanced functional features, including job status tracking, network load analysis, and market potential mapping.The study concluded that user-centric application development effectively increased process transparency, optimized customer connection efficiency, and drove strategic electricity sales growth at PT PLN (Persero).